2019
DOI: 10.7202/1065203ar
|View full text |Cite
|
Sign up to set email alerts
|

Apport de la variabilité spatiale des caractéristiques physiques du bassin versant dans la modélisation hydrologique et les sous-produits du bilan hydrologique : cas du bassin versant de l’aval Mekerra, Algérie

Abstract: Tous droits réservés © Revue des sciences de l'eau, 2019 Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…8d and 11d) is due to exceptional precipitation recorded during the last 2 years of the observation period. According to Otmane et al (2017) and Otmane et al (2019), rainfall recorded in 2008-2009 concurs in recurrences of more than a century at all stations included in this study.…”
Section: Fig 9 Spatiotemporal Distribution Of Humidity Values For Eamentioning
confidence: 74%
See 1 more Smart Citation
“…8d and 11d) is due to exceptional precipitation recorded during the last 2 years of the observation period. According to Otmane et al (2017) and Otmane et al (2019), rainfall recorded in 2008-2009 concurs in recurrences of more than a century at all stations included in this study.…”
Section: Fig 9 Spatiotemporal Distribution Of Humidity Values For Eamentioning
confidence: 74%
“…For the 1996-2010 period, some cases of extreme humidity occur along with an increase in drought conditions (62%). This is due to the climate change phenomenon affecting the region during the last decades (Talia et al 2011;Otmane et al 2019). Therefore, over the three considered periods from 1971 to 2010, the drought prevails significantly with time, accounting for 38% to 62% (1996-2010) of cases.…”
Section: Spatio-temporal Evolution Of Humidity (1971-2010)mentioning
confidence: 99%
“…In the study basin, only 29% of the rainfall that falls into the basin contributes to runoff or infiltration into aquifers. This distribu- The disparity in the distribution of the hydrological balance components in Algerian basins was also observed by Otmane et al (2019). Their study of the Wadi Mekerra basin (northwest Algeria) using the SWAT model revealed that approximately 72% of precipitation in the basin returns to the atmosphere through evapotranspiration, with only 6% generating flow into the Wadi.…”
Section: Water Balance Analysismentioning
confidence: 74%
“…Originally designed to predict water quantity and quality at the watershed level under various meteorological and spatial conditions and at different time scales (daily, monthly and yearly), SWAT can also aid in planning and decisionmaking processes aimed at environment protection and ensuring water availability for future uses (Silva et al 2015;Fatichi et al 2016). SWAT has been utilized in numerous projects worldwide (Sophocleous and Perkins, 2000;Tripathi et al 2003;Hao, 2004;Laurent, 2007;Xiang et al 2022), and has been applied in several watersheds in Algeria (Zettam et al 2017;Hallouz, 2018;Otmane et al 2019;Mami et al 2021).…”
Section: Introductionmentioning
confidence: 99%